Optimization of SnO2-Based CMOS-Integrated Gas Sensors by Mono-, Bi- and Trimetallic Nanoparticles - Robert Wimmer-Teubenbacher (Proceedings, 2020)
In this paper, we report on the optimization of SnO2-based thin film gas sensor devices by mono-, bi- and trimetallic nanoparticles. Ag, AgRu, and AgRuPd nanoparticles are sputter deposited on CMOS-integrated SnO2-thin film gas sensor devices. The CMOS device is a worldwide unique chip containing an array of eight microhotplates. The response towards the target gas CO was dramatically increased from 10% to more than 70% by using trimetallic AgRuPd nanoparticles.